Computerization methods and assessment of information intelligent level of electricity grid - Гончарова, Лідія Леонідівна (Ukrainian Information Security Research Journal, 2015)
Based on the analysis of the current state of a power network and power railways objects, it is shown that ensuringof a high level of efficiency of the electricity sectorand traffic safety is connected directly to providing highlevel of information data protection and to intellectualization of management procedures based on computer technology. Modern organization trends of railways intelligentelectric networks are examined. The methods of computer intellectualization of operation modes of a power networkare indicated. The possible methods of specializedlocal area networks organizing for intellectualization ofprocesses of power supply for traction at the level tractionsubstations are considered. The possibilities of information security level assessment in computer network sand systems using mathematical models based on thetheory of fuzzy sets are reviewed.